Rent-seeking in elite networks - Rainer Haselmann; David Schoenherr; Vikrant Vig (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2017)
We employ a unique dataset on members of an elite service club in Germany to investigate how social connections in elite networks affect the allocation of resources. Specifically, we investigate credit allocation decisions of banks to firms inside the network. Using a quasi-experimental research design, we document misallocation of bank credit inside the network, with bankers with weakly aligned incentives engaging most actively in crony lending. Our findings, thus, resonate with existing theories of elite networks as rent extractive coalitions that stifle economic prosperity.
http://hdl.handle.net/10419/130762
Keywords: F34; F37; G21; G28; G33; K39; 330